2006
DOI: 10.1097/01.csmr.0000306431.39285.0b
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced Asthma in the Competitive Cold Weather Athlete

Abstract: Exercise-induced asthma (EIA) is a very common condition that affects winter sport athletes at rates as high as 50%. It has become clear that the main etiologic factors in EIA are the extremely low humidity and high respiratory rates in these athletes, which lead to extreme airway drying. New developments in objective testing for this condition have been recently described and are reviewed here. EIA is easily treated with oral and inhaled medications. These medications are closely regulated by the antidoping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Asthma has dramatically increased in incidence over the last decade, currently affecting 235 million people worldwide . According to epidemiological surveys, a cold environmental stimulus is believed a ‘trigger’ exacerbating existing asthma symptoms, or may directly trigger asthma . Hyrkäs et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma has dramatically increased in incidence over the last decade, currently affecting 235 million people worldwide . According to epidemiological surveys, a cold environmental stimulus is believed a ‘trigger’ exacerbating existing asthma symptoms, or may directly trigger asthma . Hyrkäs et al .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] According to epidemiological surveys, a cold environmental stimulus is believed a 'trigger' exacerbating existing asthma symptoms, 8 or may directly trigger asthma. 9 Hyrkäs et al 10 surveyed 1623 young subjects and found that existing asthma increased the risks of all cold-weather related respiratory symptoms. Guo et al 11 examined the association between cold spells and paediatric outpatient visits for asthma, where cold temperatures significantly increased asthma attacks among children.…”
Section: Introductionmentioning
confidence: 99%
“…People with EIB have asthma symptoms only when they exercise (4). EIB prevalence rates vary depending on the sport and population studied, with the highest prevalence rates of 30% to 50% seen in children and adolescents, elite athletes, cold weather conditions, and high-ventilation sports (track, cross country running, soccer, ice hockey, swimming, and cross-country skiing) (1,(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, there are major differences between OC and CCR diving in terms of breathing mechanics, as the breathing valves of a CCR have very low resistance, as opposed to those in OC. However, increased respiratory resistance is only seen at high ventilation rates, such as associated with exercise above 150 watts ( Butcher et al, 2006 ), which was unlikely in both dives. Indeed, exercise intensity inferred from surface equivalent air consumption corresponded to a low- to moderate-intensity energy expenditure ( Buzzacott et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%